Study of length of umbilical cord and fetal outcome - Dharmendra Kose, Varsha; Rajendra Dode, Nikita (Journal of Neonatal Surgery, 2026)
Background: Umbilical cord (UC) length is widely regarded as a critical determinant of fetoplacental well-being and has been strongly associated with adverse perinatal outcomes. Hence; the present study was conducted for assessing correlation of length of umbilical cord and fetal outcome. Materials & methods: This prospective observational study included 200 term pregnancies (>37 weeks), with systematic intrapartum monitoring and detailed post-delivery assessment of umbilical cord characteristics, placental features, and neonatal outcomes. Data on cord length, cord complications, fetal parameters, and delivery mode were recorded and statistically analyzed using SPSS software. Results: Umbilical cord length ranged from 25–118 cm, with most cases showing normal length; short and long cords were less common but were associated with a significantly higher incidence of cord-related complications. Increasing cord length correlated with multiple nuchal loops and greater fetal heart rate abnormalities, whereas normal-length cords were predominantly associated with normal intrapartum fetal heart rate patterns. Conclusion: Normal umbilical cord length was most common and was associated with fewer cord-related complications and more stable fetal heart rate patterns. Deviations in cord length, particularly short and long cords, showed a higher association with nuchal loops, cord complications, and abnormal fetal heart rate changes, potentially influencing perinatal outcomes..